2006
DOI: 10.1242/dev.02540
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor ZBP-89 controls generation of the hematopoietic lineage in zebrafish and mouse embryonic stem cells

Abstract: Hematopoietic development is closely linked to that of blood vessels and the two processes are regulated in large part by transcription factors that control cell fate decisions and cellular differentiation. Both blood and blood vessels derive from a common progenitor, termed the hemangioblast, but the factor(s) specifying the development and differentiation of this stem cell population into the hematopoietic and vascular lineages remain ill defined. Here, we report that knockdown of the Krüppel-like transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“…Previous studies have shown that formation of the STAT3-GATA1 complex leads to the inhibition of the expression of c-globin (Ezoe et al, 2005;Foley et al, 2002;Kirito et al, 1998;Yao et al, 2009). Furthermore, the Krüppel-type zinc finger transcription factor ZBP-89 has been previously reported to interact with GATA1 and regulate expression of the globin genes and erythroid differentiation during hematopoiesis in zebrafish (Li et al, 2006;Ohneda et al, 2009;Woo et al, 2011;Woo et al, 2008). Based on these studies, we hypothesized that STAT3, GATA1 and ZBP-89 might form a multiprotein complex to regulate erythroid differentiation.…”
Section: Ptpn9 Is Required For Erythroid Cell Maturationmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have shown that formation of the STAT3-GATA1 complex leads to the inhibition of the expression of c-globin (Ezoe et al, 2005;Foley et al, 2002;Kirito et al, 1998;Yao et al, 2009). Furthermore, the Krüppel-type zinc finger transcription factor ZBP-89 has been previously reported to interact with GATA1 and regulate expression of the globin genes and erythroid differentiation during hematopoiesis in zebrafish (Li et al, 2006;Ohneda et al, 2009;Woo et al, 2011;Woo et al, 2008). Based on these studies, we hypothesized that STAT3, GATA1 and ZBP-89 might form a multiprotein complex to regulate erythroid differentiation.…”
Section: Ptpn9 Is Required For Erythroid Cell Maturationmentioning
confidence: 98%
“…Other plasmid clones for generating probes of zebrafish gata1, scl, pu.1, l-plastin, be2-globin, lyz, bmp4 and notch1b were stocks from our laboratory. Constructs for mRNA synthesis (zebrafish gata1 and zbp-89) and protein expression (human GATA1 and ZBP-89) were kindly provided by Xiangen Li (Harvard University, Cambridge, MA) (Li et al, 2006). shRNA against human GATA1 (shGATA1) and human ZBP-89 (shZBP-89) were designed as described previously (Woo et al, 2011).…”
Section: Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…48,92 Several transcription factor examples illustrate how zebrafish genetic approaches can contribute to studying hematopoietic regulatory mechanisms. New factors can be characterized functionally, and genetic interactions and epistatic relationship quickly determined in vivo (eg, znfl2a/znfl2b 93, zbp-89 94 ; the interplay of gata1 and spi1 for erythroid vs myeloid fate determination in vivo, 91 the role of the TATA box binding protein trf3 in hematopoietic specification from mesoderm via its downstream targets mespa and cdx4 95 ). Regulatory elements and mechanisms have been studied (eg, separating the elements responsible for neuronal, endothelial, and hematopoietic tal1(scl) expression, 64,96 identifying a functional ETS binding site in the lmo2 promoter, 97 and demonstrating gata1 autoregulation by self-association 98 ).…”
Section: Regulation Of Zebrafish Hematopoiesis Transcriptional Regulamentioning
confidence: 99%
“…This represents the first single gene mutation that eliminates both endothelial and hematopoietic lineages, probably in the level of hemangioblasts. Epistasis analyses have shown that cloche acts upstream of zbp-89, scl, lmo2, gata1, gata2, runx1, c-myb, fli1, flk1, tie2, hhex, and etsrp in hematopoietic and endothelial cell development in zebrafish (Stainier et al, 1995;Fouquet et al, 1997;Liao et al, 1997Liao et al, , 1998Liao et al, , 2000Brown et al, 2000;Burns et al, 2002;Patterson et al, 2005Patterson et al, , 2007Li et al, 2006;Pham et al, 2006;Sumanas and Lin, 2006). In addition, microarray analyses by comparing cloche mutant and wild-type embryos have revealed that cloche specifically regulates a panel of hematopoietic and endothelial genes (Qian et al, 2005;Sumanas et al, 2005;Weber et al, 2005).…”
Section: Molecular Pathways Involved In Hemangioblast Developmentmentioning
confidence: 99%